Migration patterns of Western High Arctic (Grey-belly) Brant Branta bernicla - Boyd, W. Sean; Ward, David H.; Kraege, Donald K.; Gerick, Alyssa A. (Wildfowl, 2013)
This study describes the seasonal migration patterns of Western High Arctic Brant (WHA, or Grey-belly Brent Geese), Branta bernicla, an admixed population that breeds in the Canadian High Arctic and winters along the Pacific coast of North America. Adult WHA Brant were captured in family groups on Melville Island (75Â°23â€™N, 110Â°50â€™W) in 2002 and 2005 and marked with satellite platform transmitting terminal (PTT) transmitters or very high frequency (VHF) transmitters. During autumn migration, all PTT-tagged Brant followed a coastal route around Alaska and staged for variable lengths of time at the following sites on the north and west coasts of Alaska: Kasegaluk Lagoon (69Â°56â€™N, 162Â°40â€™W), Ikpek Lagoon (65Â°55â€™N, 167Â°03â€™W), and Izembek Lagoon (55Â°19â€™N, 162Â°50â€™W). Izembek Lagoon was the most important staging area in terms of length of stay (two months on average) and the majority (67â€“93%) of PTT and VHF detections occurred in Moffet Bay (55Â°24â€™N, 162Â°34â€™W). After departing Izembek Lagoon, the PTT-tagged geese followed a c. 2,900 km trans-oceanic route to overwinter in the southern part of the Salish Sea (i.e. from north Puget Sound, Washington to south Strait of Georgia, British Columbia; centred at c. 48Â°45â€™N, 122Â°40â€™W). Most (c. 45%) PTT detections in the southern Salish Sea occurred in Samish Bay (48Â°36â€™N, 122Â°30â€™W) followed by Padilla Bay (48Â°30â€™N, 122Â°31â€™W; c. 26%). Brant migrated north from the Salish Sea along the coast to southeast Alaska and then followed either an interior route across the Yukon or a coastal route around Alaska. The â€œinteriorâ€ birds staged for c. four days at Liverpool Bay (69Â°20â€™N, 133Â°55â€™W) in the Northwest Territories before flying on to Melville Island. They also departed the Salish Sea two weeks later than the coastal migrants and arrived at Melville Island two weeks earlier. This study and previous research suggest that WHA Brant use similar migration routes each year and are faithful to their breeding, staging, and wintering grounds. Because WHA Brant constitute one of the smallest breeding stocks in the world (8,000â€“11,000 individuals), concentrate in only a few areas, and are likely highly site-faithful, they are susceptible to a range of threats such as excessive harvesting, habitat loss and/or degradation, and petroleum spills.